AUSTRIAN CAPITAL THEORY - BORODKIN, GURIY; E. BLOCK, WALTER (REVISTA PROCESOS DE MERCADO)
Capital theory is at the very foundation of Austrian economics. It is no exaggeration to say that, since it lies as a precursor to the Austrian Business Cycle Theory, interest rates, monetary theory, all integral to the perspective of this school of thought. The present paper is an attempt to clarify this crucially important tool of analysis for Austrian economics.